Determinan Kinerja Instansi Pemerintah Daerah - Muhamad Yamin Noch; Melyanus Bonsapia; Andarias Patiran; Harry A. Tuhumury; Victor Pattiasina (Univiversitas Dr. Djar Wattiheluw, 2021)
This study examines the Performance Determinants of Local Government Agencies in Papua Province. The test was conductedusing a sample of 77 respondents. Sampling used is purposive sampling. Data collection through surveys. Multiple linearregression that can be used to test the hypothesis. The results of this study indicate that regional financial management affects the performance of government agencies in the Papua Provincial Government, the Regional Financial Accounting System does notaffect the performance of government agencies in the Papua Provincial Government. Good governance has no effect on theperformance of government agencies in the Papua Provincial Government and finally regional financial management, regionalfinancial accounting systems, supervision and good governance simultaneously have a positive and significant effect on theperformance of government agencies in the Papua Provincial Government.